Two cases of aggressive nontumoral folliculotropic mycosis fungoides with visceral involvement. (1st October 2014) - Brugière, C.; Karanian‐Philippe, M.; Comoz, F.; Dompmartin, A.; Galateau‐Sallé, F.; Verneuil, L.
Summary: Mycosis fungoides (MF) is the most common type of primary cutaneous T‐cell lymphoma (CTCL), and folliculotropic MF (FMF) is one clinical variant of classic MF. MF generally has a good prognosis with an indolent clinical course, but for FMF greater therapeutic resistance is suggested. Visceral involvement is very rare in these two clinical forms. We report two exceptional cases of FMF with pulmonary and hepatic involvement. Five years after their initial diagnoses, patient 1 presented with a pulmonary localization of his FMF, and patient 2 with liver involvement, without lymph node or T‐cell clones in the blood. These two patients had FMF corresponding to stage T2N0M1B0. These two cases highlight the aggressiveness of this rare variant of MF. They suggest that the T lymphocytes found in the folliculotropic form of CTCL could be characterized by greater visceral tropism. They raise the question of the molecular and functional characteristics of these T lymphocytes, and the possibility of a common target in the hair follicles and certain organs. Studies have shown that chemokine receptors are likely to be involved in the skin tropism that characterizes CTCL. These two cases show the aggressiveness of FMF and point to the interest in comparing the molecular characteristics of T lymphocytes in the folliculotropic and nonfolliculotropic forms of CTCL.